Beyond fibers: The role of water and presure in skeletal muscle dynamics - Hernández Alhambra, Elena; Grasa Orús, Jorge; Calvo Calzada, Begoña (Jornada de Jóvenes Investigadores del I3A, 2025)
This study presents a computational model based on Flory-Rehner theory to analyze the response of musculoskeletal tissue. The model integrates deformation, fluid transport, and osmotic interactions, aiming to improve the multiphysics simulation of muscle behavior and to understand the role of water and interstitial pressure.